Cytokine expression profile of B. melitensis-infected goat monocyte-derived macrophages - Maurizio, Estefanía; Rossi, Ursula Amaranta; Trangoni, Marcos David; Rossetti, Carlos Alberto (Elsevier, 2023)
Brucella parasitize the macrophage where is able to replicate and modulate the immune response in order to establish a chronic infection. The most adequate response to control and eliminate Brucella infection is a type 1 (Th1) cell-mediated effector immunity. Research in immune response of B. melitensis-infected goats is relatively scarce. In this study, we first evaluated changes in the gene expression of cytokines, a chemokine (CCL2) and the inducible nitric oxide synthase (iNOS) of goat macrophage cultures derived from monocytes (MDMs) infected for 4 and 24 h with Brucella melitensis strain 16 M. TNFα, IL-1β and iNOS, and IL-12p40, IFNγ and also iNOS were significantly expressed (p < 0.05) at 4 and 24 h respectively, in infected compared to non-infected MDMs. Therefore, the in vitro challenge of goat MDMs with B. melitensis promoted a transcriptional profile consistent with a type 1 response. However, when the immune response to B. melitensis infection was contrasted between MDM cultures phenotypically restrictive or permissive to intracellular multiplication of B. melitensis 16 M, it was observed that the relative IL-4 mRNA expression was significantly higher in permissive macrophage cultures with respect to restrictive cultures (p < 0.05), independently of the time p.i. A similar trend, although non-statistical, was recorded for IL-10, but not for pro-inflammatory cytokines. Thus, the up-expression profile of inhibitory instead of pro-inflammatory cytokines could explain, in part, the difference observed in the ability to restrict intracellular replication of Brucella. In this sense, the present results make a significant contribution to the knowledge of the immune response induced by B. melitensis in macrophages of its preferential host species.